Website-Based Design of Academic Information System at Rama Chindo PAUD - Mangie Syakila Putri; Andi Christian; Muchlis (Yayasan Kita Menulis, 2026)
In line with the rapid development of technology and information, the demand for quick, accurate, and efficient information systems is growing, especially in the field of education. PAUD Rama Cindo in Prabumulih currently relies on conventional methods for managing academic data, such as grades, attendance, and student progress reports, which are recorded manually in large books and stored in physical files. This situation leads to various challenges, such as difficulties in accessing data, the potential for document loss, and inefficient information dissemination. This study aims to design and develop a website-based academic information system for PAUD Rama Cindo to enhance efficiency in managing academic data and delivering information to teachers, students, and parents. The developed system will enable digital data management, making academic information easily accessible, quick, and accurate. With this system, it is expected that academic data management can be done in an integrated and more efficient manner, while also introducing PAUD Rama Cindo to a wider community through digital media. The research methods include data collection, system design, and testing of the developed academic information system application. This study provides practical contributions to PAUD Rama Cindo in improving the quality of academic services through the application of information technology, while also offering an academic reference for the development of similar information systems in early childhood education.